O território da Mata dos Crioulos e demandas territoriais distintas: contradições entre comunidades quilombolas e unidades de conservação - Taina Goncalves Bulhoes (2016)
The use of the natural resources in a degrading way has give rise to concerns related to the destruction of the biodiversity and earth supporting capability, that led to the creation of protected natural areas intended to protect and preserve nature. At the same time, concerns have risen regarding the historical extermination of traditional people and communities, with the repression and prejudice against their cultures and exploitation of their territories and workforce. These two concepts are manifested in the territory, which is materialized in human relationships and therefore involve power struggles. The general purpose of this research is to understand the relation of the traditional communities with the forms of nature protection provided by the Government, through the territoriality performed by both. Assuming that the forms of environmental protection prohibiting the permanence and use of these natural resources by traditional communities ends in territorial and environmental conflicts harming the maintenance of these people as the effectiveness of environmental protection. The quilombola community Mata dos Crioulos is located in Alto Jequitinhonha, which overlaps, in this case, the Espinhaço hill, region that was recognized as the Espinhaço Biosphere Reservation by UNESCO and a priority area for biomass preservation. Thus, protected areas were created overlapping and involving Mata dos Crioulos, as the State Park Pico do Itambé, the Rio Preto Park and the Águas Vertentes a State Environmental Protection Area. The regulation of such protected areas regarding use of natural resources interferes in the quilombola interaction with the physical space resulting in the indication of two contradictory territoriality proposals. Therefore, is defined the main specific purpose of investigating the contradictory interests in the Mata dos Crioulos territory, located in the city of Diamantina. To understand this contradiction, responsible for the socio-environmental conflicts of this study, a territoriality analysis was performed through the follow-up of the meetings and actions from the Conselho do Mosaico do Espinhaço (Espinhaço Council), Grupo de Trabalho de Turismo (Tourism Work Group) and performing a semi-structured interview with the Preservation Unit manager. To analyse the quilombola territoriality, visits were performed and the community was interviewed. The data was analysed and applied to the FOFA matrix and generated as a result an indication of a possible territoriality coexistence, if deemed by the state that the Mata dos Ciroulos is a historical agent of environmental preservation in the region, listening and pondering their knowledge and uses for environmental preservation and territorial planning. In addition to the plausible partnership for nature, community and preservation of conservation areas, they have tourism as common possibility and potentiality, which grounded in cultural and environmental values, can generate benefits to both subjects.